Distributed admission control in multiservice IP networks : concurrency issues - Lima, Solange (2006)
In distributed admission control (AC) schemes, handling concurrent AC decisions assumes a relevant role in avoiding over or false acceptance and, consequently, service quality degradation. This problematic is even more intricate in multiservice network environments where distinct service levels need to be fulfilled. This paper debates and points out solutions to mitigate the negative impact that distributed admission of flows might have on the service level guarantees provided to network customers. Keeping in mind that simplicity is a key factor for deployable AC solutions, we suggest and discuss the use of (i) a service-dependent concurrency index; (ii) a token-based system and (iii) a rate-based credit system, as alternative or complementary proposals to minimize or solve QoS degradation resulting from AC false acceptance.